# Thread: alternating geometric sequence manipulation

1. ## alternating geometric sequence manipulation

find the sum of $\Sigma_{n=1}^{\infty} \frac{2}{3} ( {\frac{-1}{4}}^{n+1} )$

help please am I allowed to multiply by $\frac{-1}{4}^{-2}$

2. Hello, Intsecxtanx!

I hope I've guessed the problem correctly . . .

Find the sum of: . $\sum _{n=1}^{\infty} \frac{2}{3}\left(\text{-}\frac{1}{4}\right)^{n+1}$

am I allowed to multiply by $\left(\text{-}\frac{1}{4}\right)^{-2}$
Well, sort of . . . but why would you do that?

We have: . $S \;=\;\frac{2}{3}\!\left(\text{-}\frac{1}{4}\right)^2 + \frac{2}{3}\!\left(\text{-}\frac{1}{4}\right)^3 + \frac{2}{3}\!\left(\text{-}\frac{1}{4}\right)^4 + \frac{2}{3}\!\left(\text{-}\frac{1}{4}\right)^5 + \hdots$

We have a geometric series with first term, $a \,=\,\frac{2}{3}\left(\text{-}\frac{1}{4}\right)^2\,=\,\frac{1}{24}$
. . and common ratio, $r \,=\,\text{-}\frac{1}{4}$

Substitute into the formula: . $S \;=\;\frac{a}{1-r}$

3. Never mind thank you, I get it now, that's $a_1$ when you plug in n=1 and that's the numerator of the formula for the sum. Thanks!!!!